Moderate Periods of Separation of Parchish Branches in the Mother Nursery - Azamovna , Kimsanova Kholida; Khusanboy’s daughter , Tursunboyeva Mastura (Miasto Przyszłości, 2024)
The absence of scientifically based recommendations on the timing of the separation of cherry and plum grafts leads to their numerous death and sluggish development in the first field of the nursery.